STANDARISASI NILAI WAJAR DAN PENGGUNAAN METODE AKUNTANSI SEBAGAI UPAYA PENGENDALIAN PRAKTIK CREATIVE ACCOUNTING - Atik Emilia Sula; - Prasetyono (Universitas Trunojoyo Madura, 2012)
Accounting method choices offered by Indonesian Financial Accounting Standards set by Indonesia Chartered Accountant seems giving opportunities for legalization of creative accounting and earnings management practices. The presence of accounting methods constitute grey area as loopholes for every practitioners and companies to gain their intentions disregarding ethical aspect. Several motives and techniques emerging in business practice triggers tremendous impact to many aspects. According to standard setters, earnings management becomes important concern because of two reasons. Firstly, whatever the reason, earnings management practice attends to miss-lead financial statement which secondly, affects resource allocation eventually (Gumanti, 2003). Growing research found that there was a tendency to execute earnings management for short-term goals. Creative accounting and earnings management phenomenon has to be a consideration of every body such as business practitioners, academics, government, regulator, law enforcer, and communities so that even when the phenomenon could not be abolished, it can be expected to reduce negative effect comes from those two practices and preventing financial fraud that might arise from it.